Assessing the Effect of Tax Policy Changes on Compliance in Payment and Reporting by Small Enterprises: A Study at the South Bekasi Tax Office - Loen, Mishelei; Hayuningtyas, Hayuningtyas; Agustiningtyas, Indie (Taxation and Public Finance, 2025)
This study analyzes the impact of changes in MSME tax rates and tax sanctions on taxpayer compliance in terms of payment and reporting. Using a quantitative descriptive approach, data were collected through questionnaires with a purposive sampling method, involving 92 Micro, Small, and Medium Enterprises (MSMEs) in Bekasi City. Data analysis employed simple and multiple linear regression techniques. The results show that MSMEs tax rates have a positive and significant effect on taxpayer compliance, with a coefficient of determination of 0.434. Tax sanctions also positively and significantly influence compliance. Moreover, both tax rates and sanctions have a combined positive and significant impact on fulfilling tax obligations. This indicates that changes in tax policy can directly affect the compliance behavior of small businesses. Partial and joint effects demonstrate that both elements are important in shaping tax behavior. The study suggests that tax authorities should implement fair, transparent policies, supported by effective communication and education. Simplifying procedures and offering support can foster greater voluntary compliance, ultimately strengthening the relationship between MSMEs and the tax office. These findings underline the need for a balanced approach that integrates enforcement with facilitation to enhance tax compliance among small enterprises.